Fodder productivity and digestible energy value of oat (Avena sativa L.) cultivars and breeding lines under the conditions of the Northern Trans-Urals - M. N. Fomina; Yu. S. Ivanova; N. A. Bragin; M. V. Bragina (Труды по прикладной ботанике, генетике и селекции)
Background. Spring oats play an essential role in the search for a comprehensive solution of urgent problems associated with the development of a solid fodder resource base that could meet the need of animal husbandry for high-quality feeds. Adequate animal feeding is possible when high-quality fodders are available and the rations are well balanced in basic nutrients.   Materials and methods. Field studies were conducted in Tyumen Province on the experimental field of the Research Institute of Agriculture for the Northern Trans-Ural Region in 2016–2023. The tested materials included spring oat cultivars and breeding lines, with cv. ʻTalismanʼ serving as the reference. Productivity was assessed according to the harvested dry matter, crude and digestible protein, crude and digestible fat, crude and digestible fiber, and crude and digestible nitrogen-free extracts (NFE). To do this, the yield of green biomass in the phase of milky ripeness was taken into account, and the contents of dry matter and nutrients in it were measured.   Results. Promising breeding lines were evaluated for their fodder productivity (green biomass yield and the collected dry matter, protein, fat, fiber, and NFE). Digestible energy value of the tested oats was calculated in feed units (FU) and in joules of metabolizable energy (ME) and gross energy (GE). Energy digestibility (ED) and concentrations of digestible energy (DE) andmetabolizable energy (ME) were measured.   Conclusion. Cvs. ʻTobolyakʼ, ʻRaduzhnyʼ and ʻSiriusʼ were the best in fodder productivity. Cvs. ʻMegionʼ, ʻOtradaʼ, ʻFomaʼ, ʻTobolyakʼ, and line TM 07-95-16 were identified for the highest digestible energy value. They provided 0.85–0.86 FU per 1 kg of dry matter and formed 835.5–842.5 kJ of ME and 1708.1–1734.6 kJ of GE per 100 kg of dry matter. Their ED was 63.5–65.8 %, with 1092.87–1141.36 kJ/kg of DE and 896.15–935.91 kJ/kg of ME.